Pengaruh Karakter dan Pendapatan Nasabah terhadap Kolektibilitas Kredit pada Produk Kreatif di Perumda BPR - Fauzi Abdullah, Muhdas Nur; Jalalludin, Jalalludin (Ma'soem University, 2025)
Based on the results of observations and interviews, the background of this research is the level of credit collectibility in KREATIF products which increases every year. This study aims to determine the influence of character and customer income, both partially and simultaneously on credit collectibility on KREATIF products at Perumda BPR Bank Sumedang Tanjungsari. The object of research in this thesis is KREATIF product customers at Perumda BPR Bank Sumedang Tanjungsari. The type of research is quantitative associative with primary data. Data collection techniques in the form of observation, interviews, literature studies, and questionnaires. The sample technique used is non probability sampling and the type of sample in this study is accidental sampling. The population was 617 customers with a sample of 87 customers. The results showed that there was an effect of character on collectability of 0.421 or 42.1%, income on collectability of 0.234 or 23.4%, and simultaneously the effect of character and customer income on credit collectibility on KREATIF products at Perumda BPR Bank Sumedang Tanjungsari was 0.434 or 43.4%.